SPE Annual Technical Conference and Exhibition 2003
DOI: 10.2118/84152-ms
|View full text |Cite
|
Sign up to set email alerts
|

Safety Critical Systems Principles Applied to Drilling Engineering and Well Services Software

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractDrilling and Well Services software such as casing design, directional collision avoidance scans and well control applications were introduced as Safety Critical Systems in the paper SPE 73893. A serious, undetected failure in the development or use of one of these products could result in loss of life or catastrophic environmental damage. It was concluded that safety-critical software should only be used within the strict confines of a controlled management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The potential influence of some of the drilling-and-completions applications on operational safety and integrity has been formally recognized for nearly a decade (Sawaryn et al 2003(Sawaryn et al , 2006. The applications treated in this way included casing-and-tubing design, well positioning and directional surveying, pore-pressure and fracture-gradient prediction, and measurement and well control.…”
Section: Portfolio Content and Managementmentioning
confidence: 99%
“…The potential influence of some of the drilling-and-completions applications on operational safety and integrity has been formally recognized for nearly a decade (Sawaryn et al 2003(Sawaryn et al , 2006. The applications treated in this way included casing-and-tubing design, well positioning and directional surveying, pore-pressure and fracture-gradient prediction, and measurement and well control.…”
Section: Portfolio Content and Managementmentioning
confidence: 99%
“…Increased automation of the workflows associated with these tasks means that most calculations must be taken for granted and will pass unchecked. Sawaryn et al 6 have described a process for managing these systems, and identified a number of requirements related to the equations they use. Specifically, equations must be traceable back to the source documentation, which must clearly explain their purpose, limitations, and use.…”
Section: Safety and Businessmentioning
confidence: 99%
“…However, this can give rise to random differences between software packages. 6 A better method is to develop series expressions that enable a smooth transition to be maintained.…”
Section: Safety and Businessmentioning
confidence: 99%
“…One solution adopted by Zaremba is to define a suitably small number at which the expression jumps abruptly to the asymptotic value 2 . However, this can give rise to random differences between software packages 6 . A better method is to develop series expressions that enable a smooth transition to be maintained.…”
Section: Angular Changementioning
confidence: 99%